Morbidity and mortality revue of the French group of transoral robotic surgery: a multicentric study. Issue 1 (March 2016) - Aubry, K.; Vergez, S.; Mones, E.; Moriniere, S.; Choussy, O.; Malard, O.; Dolivet, G.; Lallemant, B.; Ceruse, P.
Abstract Transoral robotic assisted surgery (TORS) represents an innovative endoscopic therapeutic alternative in the treatment of head and neck tumors. Many publications favor this surgery, especially in terms of functional results. The aim of this study was to investigate the TORS morbidity and mortality and to identify the risk factors for complications. It is a multicenter retrospective study. All head and neck tumor patients treated by TORS were included in the study over a period of 5 years (2009–2014). The studied parameters were the intraoperative and post-operative complications including hemorrhage, fistula, tracheotomy, aspiration pneumonia and death. The parameters were correlated with age, tumor location, tumor stage, endoscopic exposure and patient's co-morbidities. 178 patients were included in the study. Malignant tumors classified as T1 were found in 169 cases (n  = 51), T2 (n  = 100), T3 (n  = 16) and T4 (n  = 2). The tumor locations were distributed as follows: larynx (n  = 84), oropharynx (n  = 51), and hypopharynx (n  = 43). Fifty-three patients followed post-radiation therapy. We observed 12 intraoperative complications including 6 hemorrhage, 3 pharyngeal fistulas and 3 external surgical conversions. Postoperatively, we detected 33 hemorrhage, 27 aspiration pneumonia, 9 tracheostomy, 2 pharyngostomes, 2 cervical spondylitis and 2 deaths. The risk factors identified were (i) anticoagulant and/or antiplatelet therapy for hemorrhage, (ii) tumoral stage and the laryngeal location for aspiration pneumonia and (iii) laryngeal location for tracheostomy. Higher age over 65 years has been identified as a risk factor for all post-operative complications. TORS is a safe technique for the treatment of head and neck tumors. We identified some risk factors for complications which should systematically be studied in order to reduce its morbidity.